KONSUMSI NUTRIEN BABI GROWER PERSILANGAN LANDRACE YANG MENGKONSUMSI PAKAN CAIR FERMENTASI BERBAHAN BIJI ASAM - Redempta Wea; Andy Yumima Ninu; Bernadete Barek Koten; Melkianus Dedi Same Randu (Partner, 2023)
A study aimed at studying the nutrient consumption of Landrace cross pigs consuming fermented liquid feed made from tamarind seeds with different percentages was carried out in August 2022. The study used a randomized block design (RBD) with 4 treatments and 3 replications: R0 = fermented liquid feed (FLF) containing 0% tamarind seeds (TS), R10 = FLF 10% TS, R20 = FLF 20% TS, and R30 = FLF 30% TS. Data were analyzed using analysis of variance and Duncan's further test. The research variable are the consumption of dry matter, crude fiber, and crude fat. The results showed that increasing the percentage of tamarind seeds had a significant effect (P<0.05) on dry matter, crude fiber, and crude fat consumption and caused increased dry matter and crude fiber, but decreased crude fat consumption of grower pigs. In conclusion, the percentage of using the best tamarind seeds is 30%.Key Words:  Rations, Bioconversion, Nutrients, An Aerobes, Swine, Anti-Nutrition